Conceptualisation of Poverty and Poverty Eradication Policy Performance in Uganda - Abel, Dr. Mucunguzi (IJRDO - Journal of Business Management, 2017)
The objective of the study was to determine the official and other definitions of poverty that have been used by government and other important actors in Uganda so as to contextualize the official government concept of poverty. This emanated from the research problem that poverty policies in Uganda have not scored expected successes. To reach the bottom of the inquiry, it was hypothesised that “the way poverty is conceptualized in a given society significantly affects the way it is tackled through policy enactments”. Emphasis was therefore placed on answering the following research questions: how do the different entities in Uganda define poverty; who participates in defining poverty in Uganda; by which criteria is poverty defined and why; and does the way in which poverty is defined in Uganda affect the way the government designs poverty eradication policies? A quantitative and qualitative research methodology was employed by use of questionnaire, interviews and focused group discussions (FGDs) in selected districts of Uganda. This research paper presents and discusses the data in response to these research questions.